Growth and body condition variation of the giant mudskipper Periophthalmodon schlosseri in dry and wet seasons - Quang, Dinh Minh (Academia Journal of Biology, 2016)
This study provides information on the growth and body condition variation of the giant mudskipper Periophthalmodon schlosseri between gender and fish size during dry and wet seasons. A total of 367 fish specimens was collected along mudflat and mangrove forest in Tran De from May 2014 to April 2015. The sex ratio of this fish was nearly 1:1. This species showed isometric growth as its slope value was close to the standard threshold (e.g., 3), and its length-weight relationship was similar in both dry and wet seasons. Although the condition factor of this mudskipper varied with seasonal change and fish size, it was similar in males and females and close to well-being value (e.g., 1). These results indicated that this fish lives well and can become a potential fish for aquaculture in this area, and provides useful information for our knowledge to other gobiid fishes.